(untitled) (International Journal of Engineering and Computer Science, 2013)
This paper presents a novel, yet simple zero-voltage switching (ZVS) interleaved boost power factor correction (PFC) ac/dc converter used to charge the traction battery of an electric vehicle from the utility mains. The proposed opology consists of a passive auxiliary circuit, placed between two phases of the interleaved front-end boost PFC converter, which provides enough current to charge and discharge the MOSFETs’ output capacitors during turn-ON times. Therefore, the MOSFETs are turned ON at zero voltage. The proposed converter maintains ZVS for the universal input voltage (85 to 265 Vrms ), which includes a very wide range of duty ratios (0.07–1). In addition, the control system optimizes the amount of reactive current required to guarantee ZVS during the line cycle for different load conditions. This optimization is crucial in this application since the converter may work at very light loads for a long period of time. Experimental results from a 3 kW ac/dc converter are presented in the paper to evaluate the performance of the proposed converter. The results show a considerable increase in efficiency and superior performance of the proposed converter compared to the conventional hard-switched interleaved boost PFC converter